Pelestarian Arsip Statis Melalui Perancangan E-Katalog Berbasis Website Sebagai Warisan Budaya Tak Benda - Aria Mulyapradana; Muhammad Rizaludin; Najma Varadiva; Silvia Zahrotul ‘Azizah (Pusat Riset dan Inovasi Nasional, 2026)
The focus of this research is to address crucial issues related to the maintenance and accessibility of archives of historical and cultural significance, particularly Intangible Cultural Heritage (ICH). Although archives are physically classified as tangible cultural heritage, their information content often serves as an essential record of ICH practices, traditions, and knowledge, making them a vital foundation for their preservation. The approach applied in this research is the Research and Development (R&D) method, with an emphasis on the design and implementation of a Website-Based E-Catalog. The research process includes four main stages: (1) identification and description of archives related to ICH; (2) formulation of a metadata model relevant to cultural dimensions and digital challenges; (3) construction of an e-catalog system through a website platform; and (4) validation of the system in terms of usability and ease of access for users. The research findings demonstrate that the resulting e-catalog design successfully provides a secure, organized, and accessible digital medium for archives. This e-catalog not only serves as an effective information retrieval tool, but also fundamentally transforms the archiving process from merely passive physical conservation to a proactive knowledge dissemination activity. Therefore, archives containing WBTB information can be widely accessed by scientists, academics, and the general public, directly supporting efforts to preserve, educate, and transfer WBTB to future generations. A significant contribution of this research is the realization of an integrated concept that combines modern archival technology with cultural heritage preservation efforts.